Macronuclear DNA of the hypotrichous ciliate Oxytricha fallax - Rae, Peter M. M. (1978)
DNA in the macronuclei of Oxytricha fallax, as in other hypotrichous ciliate protozoa, exists as small, achromosomal molecules rather than in chromosomes. We report studies on O. fallax DNA using physicochemical procedures and nucleic acid hybridization. Macronuclear DNA molecules range in size from 22 kilobase pairs (kb) to about 0.5 kb. The DNA has a buoyant density in CsCl of 1.694 g·cm(-3) and a melting temperature in 15 mM NaCl/1.5 mM sodium citrate, pH 7, at 65.4°. These values correspond to 34.7% Gua + Cyt and 28.1% Gua + Cyt, respectively, and base composition determined by thin-layer chromatography of nucleotides is 32.4% Gua + Cyt. The only modified nucleotide that is detectable is N(6)-methyldeoxyadenylate (0.2%), and the amount and kind of modification cannot account for the discrepancies in nucleotide composition determination by the three methods. The genes for 25S and 19S rRNA are contained in DNA molecules 6.67 kb in length, of which at least 6.15 kb is transcribed. These rDNA molecules show no intrastrand complementarity as does rDNA in some other lower eukaryotes, and they have two asymmetric sites recognized by endonuclease EcoRI. The genes for 5S RNA are in DNA molecules 0.69 kb in length. Digestion of this DNA with restriction enzymes BamHI, BsuI, HhaI, and TaqI gives no evidence for a tandemly repeated sequence. It is likely that both 19S + 25S rRNA genes and 5S RNA genes in the Oxytricha macronucleus exist as single transcription units, and both may have “spacer” regions approximately 0.5 kb long.